Biomonitoramento do Baixo Jacuí: avaliação de pesticidas e seus efeitos em peixes - Marins, Aline Teixeira (2020)
Potentially polluting anthropic activities have increased as a result of human population growth. Consequently, more contaminants are introduced into the environment, such as pesticides. The Lower Jacuí hydrographic basin is located in a region of high agricultural and livestock production, however, it lacks studies on the presence of pesticides in water samples as well as on their effect on non-target organisms. In this way, the objective of this thesis was to identify and evaluate the effects of pesticides present in the Lower Jacuí hydrographic basin, in the city of Cachoeira do Sul, RS, using silver catfish (Rhamdia quelen), lambaris (Astyanax spp.) and Nile tilapia (Oreochromis niloticus) as bioindicator organisms. Monitoring of pesticides was carried out on environmental samples collected in the Jacuí River, at three sampling points in the city of Cachoeira do Sul, RS. In 2016, monthly collections were made and in 2017, seasonal collections. A total of 23 pesticides were detected in water samples. The chemical groups that showed the highest frequency were triazine, neonicotinoid, triazole, and strobilurin. Among the pesticides detected, only four have limit values established by Brazilian environmental legislation (2,4-D, atrazine, carbaryl, and simazine), with samples below these. Two banned organophosphates were detected in 2016: azinphos-ethyl and trichlorfon. The leaching of pesticides from adjacent crops is evident, as well as insecticides used in animal production, representing a possible risk to aquatic organisms. In Manuscript 1, the objective was to verify responses in biochemical biomarkers in Nile tilapia exposed to atrazine, azoxystrobin and imidacloprid, the most frequently detected pesticides in 2016, in isolation and association (Mix) way, at environmental concentrations. The Mix group was responsible for the largest number of changes, probably due to the combined effects of pesticides. These responses in the Mix group show the potential of pesticides to induce oxidative stress and changes in the antioxidant system and acetylcholinesterase (AChE) activity, being a risk since in the natural environment aquatic organisms are exposed to a wide variety of compounds. In Manuscript 2 silver catfish were exposed to the insecticides imidacloprid and propoxur, alone and in combination. We demonstrated that these pesticides, in environmentally relevant concentrations, inhibited AChE activity in brain tissue and altered biomarkers related to the redox balance in the analyzed tissues. In Manuscript 3, biomonitoring was carried out on the Jacuí River, together with the collection of environmental samples in 2017. It was found that the presence of pesticides in the Jacuí River was associated with changes in the biochemical biomarkers of the collected lambaris. In general, in this thesis, there was a wide diversity of pesticides in the Jacuí River, as well as, even in environmental concentrations, the pesticides used in the bioassays induced greater changes in biomarkers when in association than in exposure to the isolated compound. These results trigger an alert for further studies to be carried out to increase the understanding of the effects of the environmental contaminant interactions.